2020
DOI: 10.1111/myc.13181
|View full text |Cite
|
Sign up to set email alerts
|

Role of arthroconidia in biofilm formation by Trichosporon asahii

Abstract: Background: Trichosporon asahii is the major causative agent of disseminated and deep-seated trichosporonosis. It is capable of forming biofilms on surfaces, leading to medical device-related infection. Trichosporon asahii may be present as yeast form, hyphae and/or arthroconidia; however, the relationship between its biofilm-forming ability and its morphological transition is unclear. Objectives: We investigated whether the T. asahii morphological transition contributes to its biofilm formation. We also deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…In the literature, polymorphism is defined as the ability of a fungus to take more than two different morphological forms (Mayer et al, 2013). Candida albicans provides a classic example for polymorphic pathogenic fungi, where it can form biofilms, different morphotypes for the single-celled blastospores (yeast phase), hyphae, and pseudo-hyphae (Odds and Kerridge, 1985;Kurakado et al, 2020). Formation of biofilm at the interface of yeast-to-hyphae transition was also observed for N. capsellae in this study.…”
Section: Morphological Plasticity Pathogen Biology and Disease Epidemiologysupporting
confidence: 69%
See 2 more Smart Citations
“…In the literature, polymorphism is defined as the ability of a fungus to take more than two different morphological forms (Mayer et al, 2013). Candida albicans provides a classic example for polymorphic pathogenic fungi, where it can form biofilms, different morphotypes for the single-celled blastospores (yeast phase), hyphae, and pseudo-hyphae (Odds and Kerridge, 1985;Kurakado et al, 2020). Formation of biofilm at the interface of yeast-to-hyphae transition was also observed for N. capsellae in this study.…”
Section: Morphological Plasticity Pathogen Biology and Disease Epidemiologysupporting
confidence: 69%
“…However, the release of cylindrical arthrospores by autolysis of the original hyphal wall also occurred when arthrospores were produced from multi-celled macroconidia (Figure 10). There is evidence that arthrospores are a superior asexual spore type providing enhanced dissemination and better establishment on the host tissue by protecting cells from host lytic enzymes ( Duran et al, 1973), increasing antibiotic production (Nash and Huber, 1971;Queener and Ellis, 1975), and by promoting surface adherence (Kurakado et al, 2020).…”
Section: Arthrospore (Arthroconidia) Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…T. asahii has morphological forms: yeast form, hyphae (filament form) and arthroconidia (chains of cells and asexual spores) 4 . Furthermore, arthroconidia of T. asahii may play a key role in biofilm formation by promoting cellular adhesion 15 . T. asahii is therefore a highly problematic clinical pathogen 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Culture of T. asahii. The T. asahii strains (MPU105, MPU107, MPU108, MPU113, MPU120, MPU129, MPU131, MPU133, MPU147, MPU153, MPU159, MPU160, MPU161, MPU162, MPU330, MPU331, and MPU344) used in this study were stocked in the previously reported MPU library 45 . T. asahii strains were grown on Sabouraud dextrose agar (1% hipolypepton [Nihon Pharmaceutical Co., Ltd., Tokyo, Japan], 4% dextrose and 1.5% agar [both from FUJIFILM Wako Pure Chemical Industries, Osaka, Japan]) and incubated at 27°C for 2 days.…”
Section: Methodsmentioning
confidence: 99%